Pertumbuhan dan Efektivitas Realisasi Anggaran Belanja pada Dinas Pekerjaan Umum dan Tata Ruang Kabupaten Buleleng - Ni Nengah Putri Yani; I Gusti Ayu Purnamawati; Gede Adi Yuniarta (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: The research aims to analyze the growth and effectiveness of budget realization at the Public Works and Spatial Planning Agency (Dinas Pekerjaan Umum dan Tata Ruang) of Buleleng Regency during the 2020–2024 period, as well as identify the factors that influence it and the efforts made to improve performance. Research methods: The study employed a descriptive quantitative method using growth and effectiveness ratio analyses based on the Budget Realization Report, supported by interview data. Findings: The growth of budget realization fluctuated throughout the 2020–2024 period. A significant decline occurred from 2021 to 2023, reaching –49% (a very low category), primarily due to decreases in both capital and operational expenditures. Meanwhile, the effectiveness analysis revealed that the level of budget realization varied across expenditure types. Operational expenditures (employees, goods and services, and grants) were categorized as effective, with an average realization rate above 90%, while capital expenditures showed relatively lower effectiveness, ranging from 51% (ineffective) to 88% (fairly effective). Implication: These findings indicate that the budget management of PUTR Buleleng has been well implemented in operational aspects, but still requires improvement in optimizing capital expenditures. The main influencing factors include: inadequate planning, procurement processes, and delays in tender.